ENERGY USE PERFORMANCE IN THE BUILDING COOLING SYSTEM USING A TERMOSTAT CONTROL, ON / OFF DIGITAL AND FUZZY LOGIC - Henry Nasution (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2011)
In this study, an alternative solution to reduce energy consumption in building airconditioning system is proposed and introduced. The operation and energy consumption of the system operated as either with the new control system or with the traditional on/off control were compared. Measurements were taken during the experimental period at a time interval of one minute for a set point temperature of 22 and 23o C. The room temperature, energy consumption and energy-saving ware analyzed. The main objective is to determine the amount of energy saved when a digital on/off and fuzzy logic controller is applied to the air-conditioning system. The experimental results show that significant energy savings of approximately 24 to 43% for digital on/off and 48 to 73% for fuzzy logic control were obtained. The results also indicated that the digital on/off and fuzzy logic control can save energy and improve indoor comfort significantly for building AC system compared to the thermostat control technique.